From colonial legacies to promising futures? Unpacking the Daniels v. Canada decision and the future of the Métis - Martel, Karine (2020)
After years of existing in jurisdictional limbo, the Métis have finally been handed down a Supreme Court declaration affirming that they too, alongside the Inuit and First Nations peoples, fall under the federal government’s jurisdiction over “Indians and Lands reserved for the Indians” as outlined under Section 91(24) of the Constitution Act, 1867. While the April 2016 decision in Daniels v. Canada did remove a significant obstacle for the Métis in the pursuit of rights recognition and meaningful negotiations with the federal government, the decision is worth unpacking. This thesis critically examines the Daniels decision from a Métis and decolonizing lens, and explores the potential outcomes and implications of this decision for the Métis. What this thesis finds that this decision has been achieved by relying on colonial concepts of history, Métis identity, as well as colonial expansionist and assimilationist goals from centuries ago. As for the future of this decision, this thesis finds that it remains largely unsolved, but holds great potential- despite the core of the decision being purely about jurisdiction. October 2020